New western Pacific records of Homolidae De Haan, 1839, with descriptions of new species of Homolochunia Doflein, 1904, and Latreillopsis Henderson, 1888 (Crustacea: Decapoda: Brachyura) - Richer De Forges, Bertrand; Ng, Peter K. L. (Zootaxa, 2008)
Several species of rarely reported deep-sea homolid crabs are recorded from various locations in the western Pacific: Homola ikedai, H. mieensis, H. coriolisi, Homolomannia occlusa, Homolochunia kullar, H. valdiviae, H. gadaletae, Lamoha superciliosa, L. longipes, L. longirostris, L. inflata and Yaldwynopsis saguili. Two new species are described as new, Homolochunia menezi n. sp., from the Solomon Islands and Latreillopsis trispinosa n. sp. from the Philippines.